Development of Assessment Instruments Based on Higher Order Thinking Skills (HOTS) in Thematic Learning of Grade IV Elementary School Students - Purwaningsih, Nining; Utaminingsih, Sri; Surachmi, Sri (Universitas Muria Kudus, 2022)
This study aims (1) develop a HOTS-based assessment instrument to measure the analytical and creative thinking skills of fourth grade elementary school students (2) analyze the effectiveness of the HOTS-based assessment instrument to measure the analytical and creative thinking skills of fourth grade elementary school students. The development of the HOTS-based assessment instrument adopts the 4D model developed by Thiagarajan, Semmel Semmel those are : Define, Design, Development, and Disseminate stages. The product trial design consists of product validation and test instrument testing. The subjects of the research trial included 3 teachers and 30 students of fourth grade of elementary school in Dabin 3, Jepara District. Analysis of product quality data uses validity, reliability, level of difficulty and differentiating power. Meanwhile, data analysis of feasibility and students' thinking skills uses analysis of ideal assessment criteria. The results showed that the instrument of HOTS-based assessment met content validity by the agreement of expert judgment with the percentage result of material aspects 94%, construction aspects 92% and language aspects 90% . Those are good categories. Furthermore, the results of the analytical thinking ability test of 52% of students are in the medium category, and 37% of students' creative thinking skills are in the medium category. The conclusion of this study is the development of the instrument of High Order Thinking Skill (HOTS) – based assesment is needed by teachers to carry out the learning assessment process to train and measure students' thinking skills.